Development of Prototype of Arduino-Based Automatic Ablution Faucet to Save Water Usage - Jamil, Abdillah; Imran, Al; Firdaus, Firdaus; Ana Laila Sari, Dessy (Journal of Electrical Engineering and Informatics, 2025)
This study aimed to design and develop a prototype of an Arduino-based automatic ablution faucet to minimize water consumption and promote sustainable resource use in worship facilities. This study employed an engineering research approach using a prototyping method that included system analysis, hardware and software design, prototype construction, and performance evaluation. The developed system integrates a proximity sensor to automatically control the opening and closing of the faucet, a water flow sensor to measure water usage, and an LCD display to present real-time consumption data. Functional and usability evaluations were conducted according to the ISO 25010 standard through direct testing and user questionnaires involving 30 mosque congregants. The results indicated that the prototype effectively reduced water usage by an average of 44.03% compared to manual faucets, achieved a 100% functionality score from expert assessments, and received a usability rating of 87.8%, classified as “very effective.” These findings demonstrate that the system performs accurately, efficiently, and conveniently for small-scale mosques. The novelty of this research lies in combining the ISO 25010-based quality evaluation with a real-time monitoring system to ensure measurable performance and reliability. This innovation contributes to the advancement of intelligent water-saving technologies and supports environmental conservation through the integration of automation, sustainability, and user-centered design in the context of Islamic practices.